Aneuploidy and recombination in the human preimplantation embryo. Copy number variation analysis and genome-wide polymorphism genotyping. Issue 4 (April 2020) - Konstantinidis, Michalis; Ravichandran, Krithika; Gunes, Zeynep; Prates, Renata; Goodall, N-Neka; Roman, Bo; Ribustello, Lia; Shanmugam, Avinash; Colls, Pere; Munné, Santiago; Wells, Dagan
Abstract: Research question: What are the incidence and patterns of meiotic trisomies and recombination separately and in relation to each other at the blastocyst stage via single nucleotide polymorphism genotyping combined with array comparative genomic hybridization. Design: Single nucleotide polymorphism microarrays were carried out on a total of 1442 blastocyst stage embryos derived from 268 fertile couples undergoing preimplantation genetic diagnosis for the purposes of avoiding transmittance of known single gene disorders to their offspring; 24-chromosome aneuploidy screening via array comparative genomic hybridization was carried out in parallel. Results: One hundred per cent of meiotic trisomies identified in these embryos were of maternal origin and their incidence increased significantly with advancing maternal age ( P < 0.0001). A total of 55.8% of meiotic trisomies were meiosis I-type and 44.2% were meiosis II-type. Certain chromosomes were affected more by meiosis I-type errors, whereas others experienced more meiosis II-type errors. A detailed recombination analysis was carried out for 11, 476 chromosomes and 17, 763 recombination events were recorded. The average number of recombination sites was 24.0 ± 0.3 for male meiosis and 41.2 ± 0.6 for female meiosis (autosomes only). Sex-specific differences were observed in the locations of recombination sites. Comparative analysis conducted between 190 euploid embryos and 69 embryos presenting maternal meiotic trisomies showed similar recombination rates ( P = 0.425) and non-recombinant chromatid rates ( P = 0.435) between the two categories; differences, however, were observed when analysing embryos affected with specific maternal meiotic trisomies. Conclusions: This study yielded unique data concerning recombination and the origin of aneuploidies observed during the first few days of life and provides a novel insight into these important biological processes.